Exploring strategies to overcome extra-organisational challenges faced by community pharmacies in Sarawak, Malaysia. (15th March 2018) - Kho, Boon Phiaw; Hassali, Mohamed Azmi; Lim, Ching Jou; Saleem, Fahad
Abstract: Objectives: The aims of this research were to determine extra-organisational challenges (e.g. market competition, governing policies) faced by community pharmacies in Sarawak, the coping strategies employed to deal with these challenges and explore potential legislative changes that can attenuate the intensity of these challenges. Methods: Survey questionnaires ( n = 184) were posted to all eligible community pharmacies in Sarawak, Malaysia. The questionnaire included sections on participants' demographic data, extra-organisational challenges faced, coping strategies employed and proposals to improve community pharmacy legislations. Items were constructed based on the findings of a prior qualitative research supplemented with relevant literature about these issues. Key findings: High levels of homogeneity in responses were recorded on various extra-organisational challenges faced, particularly those economy-oriented. Strategic changes to counter these challenges were focused on pricing and product stocked, rather than services provision. Highly rated strategies included increasing discounts for customers ( n = 54; 68%) and finding cheaper suppliers ( n = 70; 88%). Legislative changes proposed that might increase their share of the pharmaceutical market were strongly supported by respondents, particularly about making it compulsory for general practitioners to provide patients the option to have their medicines dispensed in community pharmacies ( n = 72; 90%). Conclusions: Current legislative conditions and Malaysian consumer mindset may have constrained the strategic choices of community pharmacies to deal with the strong extra-organisational challenges. A long-term multipronged approach to address these issues and increased involvement of community pharmacists themselves in this agenda are required to influence practice change.